Enhancing Heat Treatment Learning for Mechanical Engineering Students: A Comparative Study of Corrosion Inhibitor Effectiveness on Aluminium Protection - Saifuddin Karim; Pradani, Yayi Febdia; Pratomo, Danang Yugo; Muhtarom, Imam; Widowati, Tamara Rahma; Wahyudi, Dian Julianto; Wulandari, Amelia Dini; Subekhi, Prido (Universitas Negeri Gorontalo, 2025)
Corrosion still remains a serious problem in the application of aluminum alloys, such as Aluminum 6061, which is one of the most widely used aluminum alloys in industries because of its high strength-to-weight ratio. However, the material degrades when exposed to aggressive environments, such as acidic, alkaline, or salty solutions, and the control of corrosion has been achieved with the use of synthetic chemical inhibitors, but the increasing concern of environmental and health risks has shifted attention to more eco-friendly alternatives. The present study aimed at evaluating the efficacy of three vegetable oils (coconut oil, palm oil, and soybean oil) as environmentally friendly corrosion inhibitors for Aluminum 6061, and the alloy coupons were subjected to three different corrosive solutions (hydrochloric acid, sodium hydroxide, and sodium chloride). A quantitative experimental procedure was employed to determine the corrosion rate through the measurement of the weight loss of aluminum coupons prior to and after the immersion, and the results showed that all three oils were able to reduce the corrosion rate when compared to the samples without any inhibitor. Among them, coconut oil gave the best protection, followed by soybean oil and palm oil, because the adsorption of the organic compounds and fatty acids in the oils onto the aluminum surface formed a thin layer that separated the metal and the corrosive environment. Consequently, the results also showed that the use of bio-based oils can be a promising alternative to synthetic corrosion inhibitors in industries that use aluminumbased materials.